VIC : an interactive video system for dynamic visualization in web and Mobile platforms - Fonseca, Benjamim (2014)
This paper presents an interactive video system that enables users to change the flow of video playback by interacting with hotspots that were predefined throughout the video streams. These hotspots are synchronized with the underlying video streams and the interactions result in smooth transitions between the preloaded targets. This approach allows the dynamic visualization of content by interacting with the hotspots and producing the consequent changes in the flow of the story. The system includes web-based and mobile video players specifically developed to deal with the interactive features, as well as a configuration tool that allows content managers to choose which pre-produced interaction possibilities will be used for a specific target audience. The interactive video solution presented herein has potential to be used as a powerful communication tool, in commercial, e-learning, accessibility and entertainment contexts.